Bioethanol production from forest residues and life cycle cost analysis of bioethanol-gasoline blend on transportation sector - Hossain N. (Elsevier Ltd, 2023)
Bioethanol; Biomass; Cost accounting; Cost benefit analysis; Cost estimating; Distillation; Feedstocks; Forestry; Fuel economy; Gasoline; Life cycle; Palm oil; Rubber; Bio-ethanol production; Bio-ethanols; Forest residue; Fuel savings; Gasoline blends; Gasoline replacement; Life cycle costs analysis; Oil palm waste; Rubber-wood waste; Transportation sector; Ethanol